2015
DOI: 10.1002/app.43057
|View full text |Cite
|
Sign up to set email alerts
|

Cardanol grafted natural rubber: A green substitute to natural rubber for enhancing silica filler dispersion

Abstract: Natural rubber (NR) usage is wide‐spread from pencil erasers to aero tyres. Carbon black and silica are the most common reinforcing fillers in the rubber industries. Carbon black enhances the mechanical properties, while silica reduces the rolling resistance and enhances the wet grip characteristics. However, the dispersion of polar silica fillers in the nonpolar hydrocarbon rubbers like natural rubber is a serious issue to be resolved. In recent years, cardanol, an agricultural by‐product of the cashew indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…As mentioned earlier, the surface modification of silica by natural astaxanthin in solution strengthens the interface force of composites. The degree of aggregation between the silica particles is reduced, thereby weakening the filler network . Therefore, it reduces the repeat destruction and reconstruction of the network, which gives rise to a lower compression heat buildup.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, the surface modification of silica by natural astaxanthin in solution strengthens the interface force of composites. The degree of aggregation between the silica particles is reduced, thereby weakening the filler network . Therefore, it reduces the repeat destruction and reconstruction of the network, which gives rise to a lower compression heat buildup.…”
Section: Resultsmentioning
confidence: 99%
“…Silica is well‐known as being a type of reinforcing agent to enhance the properties of rubber matrix and its consumption is next only to the carbon black in the field of rubber processing . Compared with carbon black, the tread rubber filled with silica has the advantages of low hysteresis loss, small rolling resistance and strong wet grasping force . Replacement of carbon black by silica has been growing steadily, especially in the tire industry, as the introduction of the “Green Tire Technology” by Michelin in 1992 .…”
Section: Introductionmentioning
confidence: 99%
“…Cure characteristics were measured by using a Monsanto R‐100S oscillating disc rheometer (ODR) according to the test methods of ASTM D 2084, at a temperature of 150°C for 30 min . The optimum cure time T c90 and scorch time T s2 of the compounds were determined.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have been reported to investigate the size of aggregates and agglomerates that build impacts on the physico‐mechanical and dynamic mechanical properties of elastomer composite and tentatively correlated with silica structure . Only a few studies have been reported to determine the particle networks and cluster formation in silica reinforced elastomers . On the other hand, many morphological studies such as three‐dimensional Transmission electron microscopy (TEM), high‐resolution TEM and Scanning electron microscopy (SEM) have been done extensively to investigate the silica dispersion .…”
Section: Introductionmentioning
confidence: 99%
“…This was due to the in situ formed silica particles being well dispersed in the rubber matrix, while the commercial silica particles were agglomerated. Mohapatra et al . presented NR grafted cardanol for enhancing silica filler dispersion.…”
Section: Introductionmentioning
confidence: 99%